Assessing the gang-level and community-level effects of the Philadelphia Focused Deterrence strategy - Roman, Caterina Gouvis (Journal of experimental criminology, 2019)
Violence reduction initiatives based on focused deterrence strategies have gained attention in recent years due to their empirical support. The evaluations have generally assessed the impact of this intervention on trends in gun violence at the aggregate level, but not at the gang level. The current study evaluates both the community- and gang-level impacts of the Philadelphia Focused Deterrence strategy.